Achieving super-broad effective absorption bandwidth with low filler loading for graphene aerogels/raspberry-like CoFe2O4 clusters by N doping - Wang, Xiangyu; Liao, Jun; Du, Rongxiao; Wang, Guohui; Tsidaeva, Natalia; Wang, Wei (Journal of colloid and interface science, 2021)
[Display omitted] •N-rGA decorated with pomegranate-like CFO clusters forms 3D porous networks.•RLmin reaches up to −55.43 dB at 15.36 GHz and 2.3 mm with a filler loading of 10 wt%.•A super-wide effective absorption bandwidth of 7.28 GHz is obtained at 2.53 mm.•At 3.3 mm, the effective absorption bandwidth completely covers X-band. A unique three-dimension (3D) porous network structure where N-doped reduced graphene oxide aerogels (N-rGA) are decorated by raspberry-like CoFe2O4 (CFO) clusters. Super-broad effective microwave absorption bandwidth (7.28 GHz) of the CFO/N-rGA composite is obtained at 2.53 mm by changing N contents. Here, the dipolar relaxation loss and conduction loss are highly sensitive to the presence of pyridinic, pyrrolic and graphitic N in the CFO/N-rGA composites. A minimum reflection loss of the CFO/N-rGA composites reaches up to −55.43 dB at 15.36 GHz with a matching thickness (2.3 mm) and low filler loading (10 wt%). Its effective absorption bandwidth completely covers X-band from 7.76 to 12.72 GHz at 3.3 mm. The high-efficiency microwave absorption of the composites mainly results from the enhanced polarization relaxation, the specific design of conductive network and the superior impedance matching. This study offers a promising technical route to explore new N-doped magnetic/dielectric composites as ideal microwave absorbers.